Occupational Tasks and Wage Inequality in Germany: A Decomposition Analysis - Miriam Koomen; Uschi Backes-Gellner (Institute of Labor Economics (IZA), 2022)
We study the role of occupational tasks as drivers of West German wage inequality. We match administrative wage data with longitudinal task data, which allows us to account for within-occupation changes in task content over time. We run RIF regression-based decompositions to quantify the contribution of changes in the returns to tasks to overall changes in the wage distribution from 1978 to 2006. We find that changes in the returns to tasks explain up to half of the increase in wage inequality since the 1990s, both at the top and the bottom of the wage distribution. Specifically, abstract tasks drive the upper wage gap, while interactive and routine tasks drive the lower wage gap. Importantly, we find low-wage occupations to have the highest routine task intensity. The association between occupational tasks and West German wage inequality is thus both stronger and different than prior research has found.
Keywords: C55; D63; E24; J31; 330; wage inequality; skills; tasks; routine-biased technical change; decomposition analysis; RIF regression